Design of Hydroponic System Using NFT (Nutrient Film Technique) Method for Lettuce (Lactuca Sativa L.) Plant - Irfan Huda; Herry Setyawan; Aji Brahma Nugroho; Fitriana Fitriana (Universitas Nusa Putra, 2023)
In this study, the hydroponic system for lettuce using the Nutrient Film Technique (NFT) method has been designed. The NFT method is a nutrient delivery method that flows nutrient-containing water and circulates it continuously, so that the roots do not easily rot. The hydroponic system designed in this study uses a DHT11 sensor to detect temperature and a pH sensor to detect pH. In addition, this study also varied the color of the light in the hydroponic system to determine the effect of light color on the growth of lettuce plants. The results of the DHT11 sensor testing showed that the temperature readings were approximately the same as the reference instrument, and the average error in the sensor readings was 1.89%. The average error of the pH sensor was 1.65%, and the average pH sensor value was 1.3%. Based on the measurement of lettuce plant growth, the highest growth was found in plants without using any light, and the widest plant was the one using yellow light with a width of 8.5 cm on day 14. The number of leaves for plants using red and yellow lights was the same, with 8 leaves.